2020
DOI: 10.1111/jfs.12812
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of tomato residuum extract with Arabic gum and dill essential oil on the shelf life improvement of trout fillets stored at chilly condition

Abstract: The objective of this study was to evaluate the effects of tomato residuum extract (TRE) dipping and Arabic gum (AG) coating enriched with dill essential oil (DEO) on the shelf life extension of refrigerated trout fillets. Gas chromatography/mass spectrometry analysis revealed that the main constituents of DEO were alpha‐phellandrene (30.17%), limonene (28.31%), and carvone (21.31%). Antioxidant activities of acetone, ethanol, methanol, cold, and hot water extracts of tomato residuum were examined using reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Ethanol solvent, as GRAS (generally recognized as safe), is commonly used in the extraction process of various products. According to previous studies, ethanol showed high efficiency in solubilizing and releasing bioactive ingredients of natural products (Barkhordari & Bazargani-Gilani, 2021;Esparvarini et al, 2022;Tavakkoli et al, 2020). Selahvarzi et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…Ethanol solvent, as GRAS (generally recognized as safe), is commonly used in the extraction process of various products. According to previous studies, ethanol showed high efficiency in solubilizing and releasing bioactive ingredients of natural products (Barkhordari & Bazargani-Gilani, 2021;Esparvarini et al, 2022;Tavakkoli et al, 2020). Selahvarzi et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…In agreement with the pH values, by increasing the storage time, the production of volatile bases such as ammonia and trimethylamine significantly ( p ≤ .05) increased; this can be related to the endogenous and exogenous (microbial) enzymes, such as protease and lipase that lead to the high TVB‐N value in the studied samples. Furthermore, lipase enzyme and autoxidation reaction of polyunsaturated fatty acids of the fish fillets produced peroxides and finally aldehyde compounds [e.g., malondialdehyde (MDA)] that caused TBARS index enhancement of the samples during prolonged storage (Barkhordari & Bazargani‐Gilani, 2021; Tavakkoli et al, 2020). In agreement with the previous research, wrapping fish fillets with edible films could significantly ( p ≤ .05) control these chemical reactions that can be attributed to the decrease of microorganism growth, oxygen, and generally gas permeation into the used package (Surendhiran et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The seeds were powdered by a homemade mill (Hardston). The powdered seeds were extracted by hydro‐distillation method using Clevenger apparatus (Simax, Pyrexfan) for 4 h (Tavakkoli et al, 2020). The extracted DEO was collected in closed vials containing anhydrous sodium sulfate for dehydration and stored at refrigeration conditions until the next use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benkhoud et al [ 104 ] incorporated thyme EO (1.3% alpha-phellandrene) to extra virgin olive oil proving its ability to preserves its nutritional quality, and sensory attributes, and, most of all, to improve its oxidative stability during long-term storage. Tavakkoli et al [ 34 ] evaluated the effects of tomato residuum extract (TRE) dipping and Arabic gum (AG) coating enriched with dill EO (DEO), with alpha-phellandrene as a main component, on the shelf-life extension of refrigerated trout fillets, and found that treatments TRE 3%-AG-DEO 2% and TRE 6%-AG-DEO 2% had significantly effects.…”
Section: Resultsmentioning
confidence: 99%